Učinek vadbe hoje na robotski napravi Lokomat na telesno zmogljivost pri otrocih in mladostnikih s ceberalno paralizo - Žen Jurančič, Marijana (Rehabilitacija (Ljubljana), 2019)
Background: Recent studies showed that aerobic capacity of children and adolescents with cerebral palsy (CP) is significantly lower compared to healthy peers. The assisted robotic gait training programs are reported to lower spasticity, improve gait pattern and general physical capacity. The aim of our study was to evaluate ton what extent could the assisted-robotic gait training improve the aerobic capacity. Methods: We included 17 children and adolescents; 16 with CP and one with hereditary spastic paraparesis. Children with CP were classified based on their gross motor function. The bicycle stress testing was performed by continuous protocol. Children were referred into assisted-robotic gait training program (16 to 18 sessions, once a day, without additional physiotherapy program, in the period of four weeks): At the end of training, the stress testing was repeated. Results: The maximal blood pressure was lower after the end of training period, but the difference was not statistically significant. We also noticed relative and absolute improvement of other variables, but none of those was statistically significant either. Participants showed relatively higher oxygen consumption, with relative drop of maximal systolic pressure and relative increase of heart frequency. Conclusions: Aerobic capacity of included children and teenagers was significantly lower than in healthy peers. Assisted-robotic gait training on Lokomat device could improve aerobic capacity, but we should include a larger group of participants to reach more reliable conclusions.
Keywords: aerobic capacity; aerobna zmogljivost; Cerebral Palsy; cerebralna paraliza; Child; efficiency; otrok; rehabilitation; robotic assisted gait training; robotizirana vadba hoje; učinkovitost